Considering citizenship in imperial Chinese history. Issue 3 (3rd April 2019) - Weerdt, Hilde De
ABSTRACT: This article problematizes the meaning and use of 'citizen' and 'subject' in the global historiography of citizenship. It argues that if in pre-twentieth-century European history citizens have also been subjects, in imperial Chinese history subjects have also been citizens. This argument is laid out in three steps. The first step, which has typically been disregarded in prior discussions on the topic, establishes that membership in some form of political community was articulated through political metaphors and illustrates this on the basis of the body metaphor. Whether and how the people's membership in the polity also constitutes them as citizens is then addressed through an overview of the rules that govern the reciprocity between those groups constituting the polity and, finally, through a discussion of the types of action open to commoners to shape especially local governance.